INITIAL IMPACT OF THE COVID-19 PANDEMIC ON THE CARE PROFILE FOR CRITICALLY-ILL PATIENTS ON HEMODIALYSIS - Gallota, Claudia; Viana, Tatiana Garcia; Augusto, Fabiana da Silva; Genovese, Regina Elena; Balda, Carlos Alberto; Carneiro, Ieda Aparecida (Cogitare Enfermagem, 2023)
Objective: to compare the care profile for critically-ill patients on hemodialysis before and during the COVID-19 pandemic. Method: an observational study carried out in a hospital from São Paulo, Brazil. The participants were critically-ill patients on hemodialysis hospitalized in 2019 and 2020. The data were collected from documents of hemodialysis sessions and from medical records. Chi-square, Mann-Whitney, Shapiro-Wilk and Fisher’s Exact tests were used for comparisons (p<0.05). Results: a total of 212 sessions were performed with 50 patients in 2019 and 873 sessions with 171 patients in 2020. In 2019, the patients were referred to intensive care and hemodialysis after 4.62 ± 6.38 and 17.26 ± 24.53 days, respectively, and in 2020 these periods corresponded to 2.21 ± 3.63 and 10.24 ± 11.99 days. There were more deaths in 2020 (p=0.01) and among patients with COVID-19 (p=0.014). Conclusion: more hemodialysis sessions were observed in 2020 when compared to pre-pandemic times, an unknown situation in the first months of the pandemic.